Corylifol A from Psoralea corylifolia L. Enhances Myogenesis and Alleviates Muscle Atrophy - Han, Yeongeun (Int J Mol Sci, 2020)
Inflammatory conditions caused by cancer, chronic diseases or aging can lead to skeletal muscle atrophy. We identified myogenic compounds from Psoralea corylifolia (PC), a medicinal plant that has been used for the treatment of inflammatory and skin diseases. C2C12 mouse skeletal myoblasts were differentiated in the presence of eight compounds isolated from PC to evaluate their myogenic potential. Among them, corylifol A showed the strongest transactivation of MyoD and increased expression of myogenic markers, such as MyoD, myogenin and myosin heavy chain (MHC). Corylifol A increased the number of multinucleated and MHC-expressing myotubes. We also found that the p38 MAPK signaling pathway is essential for the myogenic action of corylifol A. Atrophic condition was induced by treatment with dexamethasone. Corylifol A protected against dexamethasone-induced myotube loss by increasing the proportion of multinucleated MHC-expressing myotubes compared with dexamethasone-damaged myotubes. Corylifol A reduced the expression of muscle-specific ubiquitin-E3 ligases (MAFbx and MuRF1) and myostatin, while activating Akt. These dual effects of corylifol A, inhibition of catabolic and activation of anabolic pathways, protect myotubes against dexamethasone damage. In summary, corylifol A isolated from P. corylifolia alleviates muscle atrophic condition through activating myoblast differentiation and suppressing muscle degradation in atrophic conditions.